The relationship between entrepreneurial orientation and employees performance at Air Kelantan Sdn Bhd (AKSB) in Kelantan / Nor Farhah Shakirah Mohd Radzi - Mohd Radzi, Nor Farhah Shakirah (2018)
The purpose of this paper is to study the relationship between entrepreneurship orientation and employees performance. This study revealed the existence of relationship between five dimension of entrepreneurial orientation namely innovativeness, proactiveness, competitive aggression, risk taking, and autonomy with employees performance. The survey of this study is conducted on 108 employees of three branches Kota Bharu area of Air Kelantan Sdn. Bhd. (AKSB) in Kelantan. The data gathered from questionnaire are analyzed with SPSS statistical package program. This study revealed the result by two objectives. The results indicate the positive result between entrepreneurship orientations and employees performance, first objective of study shown that each dimension have accepted correlated with employee’s performance. This study also showed the result of the dimension is most practiced by employees Air Kelantan Sdn. Bhd. (AKSB) in Kelantan which competitive aggressiveness. Recommendations for future research are developed.